Hydrogen Sulfide Mediates K+ and Na+ Homeostasis in the Roots of Salt-Resistant and Salt-Sensitive Poplar Species Subjected to NaCl Stress - Zhao, Nan; Zhu, Huipeng; Zhang, Huilong; Sun, Jian; Zhou, Jinchi; Deng, Chen; Zhang, Yuhong; Zhao, Rui; Zhou, Xiaoyang; Lu, Cunfu; Lin, Shanzhi; Chen, Shaoliang (Frontiers in Plant Science, 2018)
Non-invasive micro-test techniques (NMT) were used to analyze NaCl-altered flux profiles of K+, Na+, and H+ in roots and effects of NaHS (a H2S donor) on root ion fluxes in two contrasting poplar species, Populus euphratica (salt-resistant) and Populus popularis (salt-sensitive). Both poplar species displayed a net K+ efflux after exposure to salt shock (100 mM NaCl), as well as after short-term (24 h), and long-term (LT) (5 days) saline treatment (50 mM NaCl, referred to as salt stress). NaHS (50 μM) restricted NaCl-induced K+ efflux in roots irrespective of the duration of salt exposure, but K+ efflux was not pronounced in data collected from the LT salt stress treatment of P. euphratica. The NaCl-induced K+ efflux was inhibited by a K+ channel blocker, tetraethylammonium chloride (TEA) in P. popularis root samples, but K+ loss increased with a specific inhibitor of plasma membrane (PM) H+-ATPase, sodium orthovanadate, in both poplar species under LT salt stress and NaHS treatment. This indicates that NaCl-induced K+ loss was through depolarization-activated K+ channels. NaHS caused increased Na+ efflux and a corresponding increase in H+ influx for poplar roots subjected to both the short- and LT salt stress. The NaHS-enhanced H+ influx was not significant in P. euphratica samples subjected to short term salt stress. Both sodium orthovanadate and amiloride (a Na+/H+ antiporter inhibitor) effectively inhibited the NaHS-augmented Na+ efflux, indicating that the H2S-enhanced Na+ efflux was due to active Na+ exclusion across the PM. We therefore conclude that the beneficial effects of H2S probably arise from upward regulation of the Na+/H+ antiport system (H+ pumps and Na+/H+ antiporters), which promote exchange of Na+ with H+ across the PM and simultaneously restricted the channel-mediated K+ loss that activated by membrane depolarization.